THE APPLICATION OF THE RASCH MODEL TO DEVELOP TWO-TIER MULTIPLE CHOICE HIGHER ORDER THINKING SKILL TEST ON MOTION AND FORCE - Swastika Rhea Zivanka; Haratua Tiur Maria Silitonga; Hamdani (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2022)
In Indonesia, students' higher order thinking skill is considered low and students still struggle to solve HOTS problems. One of the reasons is that students are unfamiliar with HOTS questions. This research aims to produce two – tier multiple choice test to measure students' higher order thinking skill on motion and force. The method used in this research is 4D by Thiagarajan. The test developed was validated by experts and was tested on 250 8th grade students in Pontianak. Analysis of the test used the Rasch Model to determine item fit, reliability, and difficulty levels using Winstep. Based on the qualitative and quantitative analysis, the test developed is feasible to measure students' higher order thinking skill with the content validity value score 0,84 and construct validity explained by the test 64,71%. The item reliability is excellent with the score of 0,94 but students have low consistency in answering the test. The test developed consist of 2 very difficult items, 6 difficult items, 5 easy items, and 2 very easy items.